IMPLEMENTASI KEIGO PADA WEBSITE AYANA RESORT DAN FOUR SEASONS RESORT - Ni Luh Meliyanty; Anak Agung Ayu Dian Andriyani; Wayan Nurita (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Keigo is a type of speech level that is often used by the Japanese business people, as well as in the world of tourism in Bali.  One of them is the use of keigo in marketing through website media. The data sources used are the Ayana Resort Bali website and Four Seasons Resort Bali At Jimbaran Bay  website. This study focuses on the function of the keigo speech level found on the two accommodation websites.  Data collection methods and techniques used in this study are observation methods followed by note-taking techniques, listening techniques and purvosive sampling.  Data analysis methods and techniques used are descriptive qualitative methods. While the methods and techniques of data analysis presentation using informal methods. Based on the results of the study, it was found function the level speech keigo. The use of kenjougo to express something in a condescending way to show respect for website readers. The use of teineigo  is used to make the content of the reading more polite. The function of the use of speech level markers on the two websites is to express honor, state distance, state dignity and also be found to state marketing language. The function states the marketing language found, namely, providing information, persuading, reminding and providing added value.